RELATIONSHIP OF MOTIVATION AND MIDWIFE TRAINING IN LONG TERM CONTRACEPTION SERVICE - Sri Wahyuningsih (JURNAL KEBIDANAN, 2019)
Introduction: Given the large number of births per year, efforts are needed to control birth through family planning using contraception, especially long-term ones. The use of long-term contraceptives (MKJP) includes IUDs, Implants and MOW / MOP. The aim of the study: to find out the relationship between motivation and the results of midwifery training test results in long-term contraceptive method services in Lumajang district. Research method: quantitative research using Spearman correlation test. Results: there was a low positive relationship between motivation and written test scores of trainees (r = 0.391, p = 0.033). Conclusion: The training participants 'motivation is mostly good and the trainees' written test scores are mostly good. So even though the motivation and results of the training have a low relationship, but with the maximum ability of the training participants it can still motivate participants when providing long-term contraceptive services.